IMLOVIY BILIMLARNI BAYONLAR VOSITASIDA TAKOMILLASHTIRISH - Allaberganova Marifat Kuranbayevna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
this article talks about the effective use of narration, types of narration, and their role in the student's orthography in increasing and improving the spelling literacy of elementary school students.